Das deutsche Flüchtlingsproblem - Schlenger, Herbert (ERDKUNDE, 1953)
The problem of refugees in Germany is part of a problem affecting the whole world. It provides many opportunities for geographical treatment. The settling of refugees offers material for investigations of a monographic and comparative nature. Investigations of that type are at the same time contributions towards the social geography of Germany which is now in a stage of development. Only an increased participation in world trade will allow Germany to solve its refugee problem. It seems probable that the Soviet Union was aware of this implication in 1944/45.